Religion, Higher Education, and Environmental Sustainability: Identification of Green Fiqh in Islamic Religion Courses at Muhammadiyah and Aisyiyah Universities - M Nurdin Zuhdi; Iwan Setiawan; David Sulistiawan Aditya; M Anwar Nawawi; Rizki Firmansyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Based on the ranking of 20 Indonesian Green Universities by UI Green Metric 2022, green campuses are dominated by public campuses that do not have a strong foundation in Islamic values. In fact, not a single Muhammadiyah and 'Aisyiyah Universities (PTMA) was included in the top 10 ranking release. Why has PTMA, which has developed Green Fiqh, not been able to present itself as a green campus? This research aims to identify Green Fiqh in Islamic Religion learning at PTMA. This qualitative research uses a thematic approach with a narrative-descriptive-explanative strategy. The research was conducted at three PTMAs in Yogyakarta. The findings obtained are: first, the Green Fiqh study materials in learning Islamic religion courses at PTMA are not optimal. Even though Muhammadiyah has created Green Fiqh products such as Environmental Fiqh, Disaster Fiqh, Water Fiqh and Agrarian Fiqh. Second, learning about Islamic religion at the three PTMAs where the emphasis is still limited to the basics of Islamic religious teachings, such as Aqidah, morals and worship. The Aqidah theme raised also does not optimally touch the role of rububiyah monotheism in preserving the environment. The moral theme also does not touch much on actual contemporary problems, including the problem of global climate change. Third, the Al-Ma'un ethos which is the foundation and spirit of Muhamamdiyah taught in the three meanings of PTMA has not yet developed. Al-Ma'un's main mission is only interpreted as fighting religious liars in a narrow sense. Al-Ma'un has not been developed towards